Assessing the Impact of Emotional Intelligence on Job Satisfactionamong Private School Teachers of Hyderabad, India - Mohammad, Javed (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study isto assess the level of emotional intelligence (EI) and Job Satisfaction (JS) among high school teachers of private schools in Hyderabad.The survey method was used to collect primary data from a sample of 221 teachers from selected private schools in Warasiguda, Musheerabad, Chilkalguda, Ambernagar and Ramnagar areas of Hyderabad. The standardized scales adopted for measuring the emotional intelligence (Sungouh, 2006) and job satisfaction (Pestonjee , 2002) comprise 20-item level of EI based on a five- point rating system of 1 to 5, and 80-item on-the job and off-the-job factors of JS respectively. The reliability and validity of both the scales are within the acceptable norms. The findings establish that school teachers had moderate levels of job satisfaction and emotional intelligence. Even though emotional intelligence has a significant impact on job-related aspects of job satisfaction, it has no impact on the management, personal adjustment and social relation aspects of job satisfaction. Nevertheless, the overall result shows thatthere is a significant correlation between emotional intelligence and job satisfaction among teachers in executing their jobs in the private high schools surveyed.